2017
DOI: 10.1126/science.aao6538
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ultrasmall, homogeneously alloyed, bimetallic nanoparticles on silica supports

Abstract: Supported nanoparticles containing more than one metal have a variety of applications in sensing, catalysis, and biomedicine. Common synthesis techniques for this type of material often result in large, unalloyed nanoparticles that lack the interactions between the two metals that give the particles their desired characteristics. We demonstrate a relatively simple, effective, generalizable method to produce highly dispersed, well-alloyed bimetallic nanoparticles. Ten permutations of noble and base metals (plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
279
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(297 citation statements)
references
References 34 publications
(38 reference statements)
18
279
0
Order By: Relevance
“…One example is supported catalysts,which are amultibillion Euro business worldwide, [2] and for which novel synthetic methods are continuously explored. [3][4][5] In the following it is described that aw ide range of different supported catalysts can be produced by simple milling, starting from macroscopic metal powder and as upport material, resulting in nanometer-sized noble metal (and in some cases also base metal) nanoparticles on different supports.T his approach may have very high practical value,s ince milling could become as imple alternative method to the complex solution processing nowadays used in the synthesis of supported catalysts.M oreover, nanoscale dispersion is highly interesting in many other fields,a nd thus these findings have significance also beyond catalysis.…”
mentioning
confidence: 99%
“…One example is supported catalysts,which are amultibillion Euro business worldwide, [2] and for which novel synthetic methods are continuously explored. [3][4][5] In the following it is described that aw ide range of different supported catalysts can be produced by simple milling, starting from macroscopic metal powder and as upport material, resulting in nanometer-sized noble metal (and in some cases also base metal) nanoparticles on different supports.T his approach may have very high practical value,s ince milling could become as imple alternative method to the complex solution processing nowadays used in the synthesis of supported catalysts.M oreover, nanoscale dispersion is highly interesting in many other fields,a nd thus these findings have significance also beyond catalysis.…”
mentioning
confidence: 99%
“…The XPS results of Pt/rGO indicate that Pt 0 and Pt 2+ coexist on rGO with the ratio of 1:1.5 (Figure a). As shown in Figure b, similar XRD patterns between Pt/rGO and rGO indicate highly dispersion of Pt NPs on rGO . Pt NPs dispersed on rGO perform as “spacers” to delimit the stack of rGO nanosheets which caused the intense peak at about 10°.…”
Section: Resultsmentioning
confidence: 65%
“…As shown in Figure 13b, similar XRD patterns between Pt/rGO and rGO indicate highly dispersion of Pt NPs on rGO. [38] Pt NPs dispersed on rGO perform as "spacers" to delimit the stack of rGO nanosheets [1b] which caused the intense peak at about 10°. In addition, Pt/rGO exhibited IV adsorption curve of mesoporous structure, which is due to the stacked of rGO one-dimension sheets (Figure 13c).…”
Section: Dextran-capped Pt Nps Supported On Rgomentioning
confidence: 99%
“…It has been reported that, by adjusting the pH of solution, the hydroxyl groups become protonated and thus positively charged below the point of zero charge (PZC), or deprotonated and thus negatively charged above the PZC . Therefore, metal anions like [PtCl 6 ] 2− or cations like [(NH 3 ) 4 Pt] 2+ can be strongly anchored onto the support surface via strong electrostatic adsorption, and thus isolated metal atoms stabilized on the support are obtained by subsequently removing the undesired ligands. Except for the hydroxyl groups, the surface monolayer ethylene glycol groups were also reported to absorb PdCl 4 2− for the formation of an atomically dispersed Pd catalyst under UV irradiation …”
Section: Synthesis Strategies For Single Metal Atom Catalystsmentioning
confidence: 99%